A fatal poisoning case by intravenous injection of "bath salts" containing acetyl fentanyl and 4-methoxy PV8. (October 2016) - Yonemitsu, Kosei; Sasao, Ako; Mishima, Satoko; Ohtsu, Yuki; Nishitani, Yoko
Highlights: A fatal "bath salts" poisoning case, involving acetyl fentanyl and 4-methoxy PV-8. Simultaneous quantitative analysis of both drugs was done using LC–MS/MS. Administration of the drugs was most likely to be intravenous. Abstract: A man in his 30's was found at home, not breathing. He was admitted to an emergency hospital and the doctor confirmed his death. He had a history of methamphetamine abuse spanning several years, and while fresh needle marks were visible on his arm, the only other autopsy findings indicated an acute death. A small plastic bag containing a pale brown white powder, and a small amount of liquid in a syringe were found at the scene. The police forensic laboratory detected acetyl fentanyl and 4-methoxy PV8 (4-methoxy PHPP) in both the powder and the liquid. Scan analysis by gas chromatography–mass spectrometry (GC–MS) and liquid chromatography–mass spectrometry (LC–MS) identified acetyl fentanyl and 4-methoxy PV8 in the urine sample. Both drugs were quantitated simultaneously by liquid chromatography–tandem mass spectrometry (LC–MS/MS), using the selected reaction monitoring method. The concentration of acetyl fentanyl in the femoral vein blood, urine, and gastric contents were 153, 240, and 880 ng/mL respectively, and the concentration of 4-methoxy PV8 in the femoral vein blood, urine, and gastric contents were 389, 245, and 500 ng/mL respectively. Cause of death was attributed to acute poisoning by "bath salts" containing acetyl fentanyl and 4-methoxy PV8. Evidence indicated that self-administered intravenous injection was the most likely scenario, and that the deceased had been a habitual user of the "bath salt" drug for some time. Drugs detected in the gastric contents could be explained by the gastric secretion of basic drugs, or drug-containing bile entering the gastric contents.